2011
DOI: 10.1177/0192512110378657
|View full text |Cite
|
Sign up to set email alerts
|

The bases of political trust in six Asian societies: Institutional and cultural explanations compared

Abstract: Political trust reflects people’s evaluative orientation toward the polity and is thus vital to regime stability. Based on data drawn from a cross-national social survey, this article examines the level of political trust in six Asian societies and the possible effects of a series of institutional and cultural factors on political trust. It finds that institutional factors, particularly the economic and political performance of government, are powerful determinants of political trust, whereas the effects of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 38 publications
9
99
0
1
Order By: Relevance
“…Both hypotheses were supported, lending full support to ITPT. Our findings corroborate existing studies in mainstream political science (Mishler & Rose, 2001;Stoyan, Niedzwiecki, Morgan, Hartlyn, & Espinal, 2014;Torcal, 2014;Wong et al, 2011) as well as those in tourism which found citizens' evaluation of the economic and political performance of government to be the most important determinants of political trust. The economic performance of government, rooted in the rational-choice framework, emphasizes the material sources of political trust (Zhong, 2014).…”
Section: Discussion Of Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Both hypotheses were supported, lending full support to ITPT. Our findings corroborate existing studies in mainstream political science (Mishler & Rose, 2001;Stoyan, Niedzwiecki, Morgan, Hartlyn, & Espinal, 2014;Torcal, 2014;Wong et al, 2011) as well as those in tourism which found citizens' evaluation of the economic and political performance of government to be the most important determinants of political trust. The economic performance of government, rooted in the rational-choice framework, emphasizes the material sources of political trust (Zhong, 2014).…”
Section: Discussion Of Resultssupporting
confidence: 91%
“…Items to measure interpersonal trust (1 D do not trust at all; 5 D complete trust) were borrowed from Delhey, Newton, and Welzel (2011). Respect for authority was measured using items borrowed from Shi (2001) and Wong et al (2011). The items used are presented in Table 2.…”
Section: Sample Selection and Survey Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of trust is a major foundation in ensuring the continuity of legitimacy a democratic system wields (Yani, 2015). Political trust is the hope and result of citizen evaluation over the performances of political institutions and leaders in implementing democratic values (Yani, 2015;Grimmelikhuijsen, 2012;Wong et al, 2011;Bourne, 2010). Regarding the voter participation rate, a study conducted by Grönlund and Setälä (2007) shows that political trust significantly affects voter turnout on election day.…”
Section: Kata Kuncimentioning
confidence: 99%
“…Performance can be defined by multiple constituents, since the state itself is responsible for the provision of numerous political goods. In this regard, the most basic obligations are the guarantee of democratic political rights (Clarke, Dutt, & Kornberg, 1993;Mishler & Rose, 1999;Newton, 2008;Norris, 1999;Rahmani, 2010), establishment of economic efficacy (Lipset & Schneider, 1983;Miller & Listhaug, 1999;Mishler & Rose, 2001;Wong, Wan, & Hsiao, 2011), provision of welfare services in an appropriate quality (Kumlin, 2004;Soss, 1999), and the initiation and maintenance of basic procedural justice principles in the operation of the institutional system, along with a low level of corruption (Clausen, Kraay, & Nyíri, 2011;Della Porta, 2000;Kotzian, 2011;Offe, 2004).…”
Section: Introductionmentioning
confidence: 99%